2022
DOI: 10.1111/apa.16624
|View full text |Cite
|
Sign up to set email alerts
|

Mild COVID‐19 in hospitalised infants younger than 90 days

Abstract: Clinical manifestations of COVID-19 are generally milder in children than adults. Severe acute respiratory distress syndrome is rarely reported, even though cardiovascular diseases, diabetes and chronic lung diseases have been associated with severe outcomes. 1 Children Other 36 (26%) Abbreviations: NICU, neonatal intensive care unit; OBI, brief intensive observation; PICU, paediatric intensive care unit; PED, paediatric emergency department. a Respiratory support: oxygen, high-flow nasal cannula, continuous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The majority of hospitalized children were healthy, with no underlying clinical conditions, and were admitted primarily due to concerns related their young age, as reported in other case series [ 2 , 3 , 6 , 17 , 18 , 19 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The majority of hospitalized children were healthy, with no underlying clinical conditions, and were admitted primarily due to concerns related their young age, as reported in other case series [ 2 , 3 , 6 , 17 , 18 , 19 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 89%
“…Although it is often associated with fever or URT symptoms, poor feeding can be the only symptom observed. Thus, COVID-19 should also be considered in infants with inadequate milk intake [ 9 , 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11] Data on SARS-CoV-2 infection in infants suggest that in most cases it presents as a mild disease. 12 In particular, a multicentre international study showed that only 3% of infants testing positive for SARS-CoV-2 developed symptoms consistent with bronchiolitis. 3 In the same study, SARS-CoV-2-related bronchiolitis mostly had a mild clinical course, but the number of affected infants was considerably limited.…”
Section: Original Researchmentioning
confidence: 99%